Pemahaman Konsep Pada Nilai Tempat Di Sekolah Dasar - Mulyasari, Wiwit; Fazrul Prasetya Nur Fahrozy (Jurnal Elementaria Edukasia, 2023)
Mathematics is one of the subjects that must exist at every level of education to support everyday life. Especially in the lower grades or in elementary school. In low grades, it is necessary to have a strong conceptual understanding so that misconceptions do not occur in subsequent learning, especially in learning place value. This article discusses the understanding of the concept of place value in elementary schools which needs to be considered in learning and discusses the media to support students in learning the concept of place value. The research method used in this study is a descriptive qualitative approach, using the literature review method. The data sources in this study are documents in the form of books, journals, scientific papers, and other documents that are relevant to the implementation of school culture in education. the character of courtesy and discipline of students in elementary schools. The results of the study show that there are many media that teachers can use to support learning. There are 7 learning media that can support learning to understand the concept of place value, namely number bag media, colored glass media, spedomatic media, learning trajectory, dienes blocks, number seed bag media, and number board media.